Konsepsi Penanganan Perkara Tindak Pidana dengan Restorative Justice yang Mengedepankan Kemanfaatan Hukum - I Komang Aditya Diputra; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
Indonesian society always assumes that minor criminal cases are always resolved through trials in court. With the existence of Perja No. 15 of 2020, it is hoped that it will be able to answer these problems and provide benefits to the community. (1) How are restorative justice arrangements in the current provisions of Indonesian criminal law? (2) What is the conception of restorative justice in the settlement of criminal cases from the perspective of legal benefit? The research method and problem approach used is the Normative Method with a conceptual approach. The current regulation of restorative justice is the SE Head of Police, Regulation of the National Police Chief, Perja No. 15 of 2020. The concept of restorative justice in the settlement of criminal cases is in accordance with Article 3 to Article 5 of Perja No. 15 of 2020, the conception of restorative justice in this Perja reflects the value of legal benefits. . In particular, the regulation related to the settlement of criminal acts with restorative justice is contained in Perja No. 15 of 2020. For the government, the settlement of criminal acts with restorative justice is contained in the Draft Criminal Code.